The WikiLeaks Illusion. - ROBERTS, ALASDAIR (Wilson Quarterly)
The article evaluates the impact that the organization WikiLeaks' massive release of classified documents to international news media had on opening barriers to U.S. governmental secrecy. Contrary to claims that the release of the classified documents would herald a new era of free information flow and transparency of government actions, the result has shown how resilient and durable these barriers of secrecy actually are. The author explores this conclusion.